Efeito do chá verde no processo de reparo alveolar de ratos tratados com bifosfonato - Mada, Edson Yoshihiro (2015)
Bisphosphonate (Bp) induced osteonecrosis of the jaws is considered as a significant complication when the need for surgical interventions in the oral cavity, the prevention and treatment are not yet well established. Thus, this study aimed to analyze the effect of 1% GT in the repair of dental sockets in animals treated with intravenous (IV) bisphosphonate. Sixty Wistar male rats were set in four groups according to the treatment: C group - control, animals received IV injection of 0.9% saline; GT group - animals received an intravenous injection of 0.9% saline + 1% GT in drinking water; ZA Group - treated with IV injection of zoledronic acid (ZA) + GT Group - treated with intravenous injection of ZA and 1% GT. The drug was administered at a dose of 0.035 mg/kg every two weeks. Eight weeks after the start of administration of ZA, extractions of the upper right molar teeth from all groups were obtained, when 1% GT was taken orally as the only source of water to animals of GT and ZA+GT groups. After periods of 7, 14 and 28 days of dental extractions, the animals were euthanized and specimens removed for histological and OPG, RANK, and TRAP immunohistochemistry analysis. Dental sockets from C group repaired in accordance with normal morphology and chronology. The dental socket of the experimental groups had similar morphology of repair, with persistence of the bone surface exposure over the periods associated with the accession of bacterial biofilm. The GT group showed moderate osteoclastic activity and discreet osteogenesis, while in ZA and ZA+GT groups the wound healing had not occurred up to 28 days with clear installation of osteonecrosis of the maxilla. Attention was given to TRAP immunolabeling, which presented osteoclasts in granulation tissue of ZA and ZA+GT groups. Thus, it was concluded that the intake of green tea did not improve the repair of the dental sockets compared to the control group. Similarly, also did not contribute significantly to repair the association of ZA observing the same histological characteristics when compared to animals receiving ZA alone